Nurses Viewpoints on Relationship between Components of Working System of Nurses with Patients Safety Using Sips Model - homa doroudi; reza shami; hamid Gharehbaghi (Zanjan University of Medical Sciences and Health Services, 2016)
Background and Objectives: Patient safety is a global concern that can be influenced by the components of working system in medical settings. The present study was carried out to investigate the relationship between the working systems of nursing staff with patients' safety in Zanjan hospitals in 2014. Materials and Methods: In this cross-sectional study, nurses were recruited to the study using stratified random sampling method. Regarding working systems, a modified questionnaire of the Carayon and Honaker was used to collect data. The questionnaire was arranged on a Likert type 5-score scale. The validity of the questionnaire was confirmed using the experts' viewpoints and the reliability was confirmed using the Cronbrachchr('39')s alpha coefficient (0.89). The standard questionnaire of the World Health Organization was used to collect data on patients' safety. We used the structural equation modeling in the LISREL to analyze the data. Results: Components of the system played an important role in patient safety. With probability of 99% (except for one component), there was a significant relationship between the working system and patients safety. Conclusion: Regarding the results of this study, components of working systems influenced patient safety in health care centers. To improve patientchr('39')s safety in hospitals, attention should be paid to all components of a working system to prioritize its components.